1998
DOI: 10.1002/(sici)1097-4547(19981215)54:6<840::aid-jnr12>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of insulin-like growth factor decreases motor neuron cell death and promotes muscle reinnervation

Abstract: Neonatal sciatic nerve axotomy causes motoneuron death and muscle denervation atrophy. The aim of the present study was to determine whether insulin-like growth factor-I (IGF-I) administration promotes muscle reinnervation and counteracts motor neuron loss after such an injury. Six weeks after sciatic nerve axotomy performed in 2-day-old pups, the number of motor neurons, as assessed by retrograde transport of horseradish peroxidase injected into the extensor digitorum longus (EDL) muscle, was reduced from 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…In the peripheral nervous system (PNS), IGF-1 is present in both the neurons and the skeletal muscles, and acts as a neurotrophic factor for motor, sensory, and sympathetic neurons to promote growth cone motility and neurite outgrowth. [11][12][13] It is also known that IGF-1 promotes neurite outgrowth in explants of adult rat retinas. 14 Such available evidence makes it clear that IGF-1 plays an important role in axonal regeneration and survival of CNS neurons as well as of those in the PNS.…”
mentioning
confidence: 99%
“…In the peripheral nervous system (PNS), IGF-1 is present in both the neurons and the skeletal muscles, and acts as a neurotrophic factor for motor, sensory, and sympathetic neurons to promote growth cone motility and neurite outgrowth. [11][12][13] It is also known that IGF-1 promotes neurite outgrowth in explants of adult rat retinas. 14 Such available evidence makes it clear that IGF-1 plays an important role in axonal regeneration and survival of CNS neurons as well as of those in the PNS.…”
mentioning
confidence: 99%
“…Vergani et al found that systemic IGF-1 promoted neuronal survival following crush injury and improved muscle reinnervation 34. Kanje et al found that locally delivered IGF-1 following crush injury in juveniles led to improved sensory function 35.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 exerts a protective effect against motor neuron degeneration in organotypic spinal cord cultures [9,10] and cultured motor neurons [11], and is also capable of preventing motor neuron loss following sciatic nerve axotomy in rat pups [12]. Furthermore, it was reported to be effective against motor neuron loss in wobbler mice when co-administered with glycosaminoglycans that increase its permeability to the central nervous system (CNS) [13], whereas IGF-1 administration alone had no effect [14].…”
Section: Introductionmentioning
confidence: 99%